Integrasi Kelas Virtual ke Dalam Portal Sistem Informasi Akademik Universitas Diponegoro - Affandi, Fikri Ahmad; Isnanto, R. Rizal (Transmisi, 2011)
The information system is a very important thing in education. Up until now, Academic Information Systems (AIS) at the University of Diponegoro assists in the implementation of academic activities of the administrative processes such as charge card plan of study, as well as the central database. Therefore AIS Virtual Classroom integration of Diponegoro University is needed, which adds Ajax technology (Asynchronous JavaScript and XML) and Virtual Classroom functions enriched by being able to apply some functions into a social networking site. Virtual Classroom which already integrated in Diponegoro University Academic Information Systems today still has some problems, such as speed and lack of existing application. One way that can be used to overcome these problems is to apply Ajax technology and the addition of function to send information into social networking sites in this Final Project is Twitter. The steps performed are the system requirements analysis through a study of existing Virtual Classroom on SIA and collecting various references about Ajax, system design using the modeling language UML (Unified Modeling Language), implementation and testing of the system. The results of this study indicate that the addition of Ajax on the Virtual Classroom can provide fast service to access data on choices of the system because it is done asynchronous. These systems also provide facilities for faculty and admin users because some options can be sent to Twitter via a message. Keywords: Virtual Class, Ajax, Information Systems, Social Networks, UML